How Can MSMES Achieve Sustainability Business? - Lenny Christina Nawangsari; Ahmad Hidayat Sutawidjaya (Business and Entrepreneurial Review, 2021)
In business competition, MSMEs are required not only to have working capital but also to be able to manage human resources well. One of the strategies undertaken by MSMEs to win the competition is by implementing Green Human Resources management in their HR management. This study aims to analyze the effect of Green Human Resources management which consists of Green Recruitment, Green Training & Development, Green Performance & Appraisal, and Green Compensation & Rewards on Competitive Advantage and Sustainability Business on MSMEs in Bukittinggi. The research method used is a quantitative method with statistical analysis of the Structural Equation Model (SEM). The research results confirm that Green Recruitment, Green Performance & Appraisal, and Green Compensation & Reward affect Competitive Advantage and Sustainability Business. Meanwhile, Green Training & Development does not affect Competitive Advantage and Sustainability Business. Good implementation of Green Human Resources Management at MSMEs in Bukittinggi will affect competitive advantage and Sustainability Business.